1996
DOI: 10.1037/0022-0167.43.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Nature, extent, and importance of what psychotherapy trainees do not disclose to their supervisors.

Abstract: Nondisclosures in supervision were studied for 108 supervisees. Supervisees reported an average of 8.06 nondisclosures ranging in importance level. Negative reactions to the supervisor were the most frequent type of nondisclosure. The most frequent reasons for nondisclosures were perceived unimportance, that the nondisclosure was too personal, negative feelings, and a poor alliance. The manner of nondisclosure was usually passive. Most nondisclosures were discussed with someone else, typically a peer. Supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
533
9
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(599 citation statements)
references
References 53 publications
47
533
9
10
Order By: Relevance
“…The systematic search identified 21 measurement instruments related to supervision of which five were not published in scientific journals [50–54], six were published but not as papers to validate the instrument [55–60] and 11 were published as validation studies [6171]. Additionally, three instruments were found where respondents assessed an external event [18,72,73], and one instrument related to the primary health care field [74].…”
Section: Resultsmentioning
confidence: 99%
“…The systematic search identified 21 measurement instruments related to supervision of which five were not published in scientific journals [50–54], six were published but not as papers to validate the instrument [55–60] and 11 were published as validation studies [6171]. Additionally, three instruments were found where respondents assessed an external event [18,72,73], and one instrument related to the primary health care field [74].…”
Section: Resultsmentioning
confidence: 99%
“…In this way, TCIT may be a likely candidate for non-disclosure in the supervision process. Previous supervision researchers have found that when supervisees hide information from supervisors, the supervisory working alliance is perceived to be weaker (Ladany, Hill, Corbett, & Nutt, 1996).…”
Section: Abstract: Therapist Crying Tears Emotional Expressions Sumentioning
confidence: 99%
“…In this way, TCIT may be a likely candidate for non-disclosure in the supervision process. Previous supervision researchers have found that when supervisees hide information from supervisors, the supervisory working alliance is perceived to be weaker (Ladany, Hill, Corbett, & Nutt, 1996).Thus, facilitating disclosure and discussion of TCIT may enhance the supervisory alliance.Finally, although no researchers have focused on supervision or training regarding TCIT in psychology, research has been conducted on crying amongst medical professionals. In a 2009 study of medical trainees, Sung et al (2009) found that the vast majority of medical trainees felt that discussion of physicians' crying was inadequate, and, in a recent study on tears of physicians, Majhail and Warlick (2011) emphasized the importance of supervision and "debriefing" with colleagues with regards to professionals' tears.…”
mentioning
confidence: 99%
“…Ladany, Hill, Corbett and Nutt (1996) examined this issue and found that supervisees not disclosing issues around clinical practice were intra-related to the supervisees' perceptions of the characteristics of supervision, and the scope to which supervision fit their needs, and aided their education and development.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Internally, we [emphasis added] not the larger system but frontline workers and supervisors, had failed. and other studies regarding the compatibility of administrative and educative functions of supervision (Bogo & McKnight, 2005;Caspi & Reid, 2002;Erera & Lazar, 1994a;Greenspan, Hanfling, Parker, Primm, & Waldfogel, 1994;Hung, Ng, & Fung, 2010;Itzhaky, 2001;Kadushin, 1992;Kadushin, Berger, Gilbert & Aubin, 2009;Ladany, Hill, Corbett & Nutt, 1996). There were also some leitmotifs that continued to flow over and over again in The current situation for child welfare agencies is one of coping with overwhelming budget pressures stemming from soaring caseloads and inadequate resources for addressing the more 3 complex needs of today's child welfare population (Anderson & Gobeil, 2003;Stephenson et al, 2000;Drake & Yadama, 1996;Kinjerski & Herbert, 2000;Regehr et al, 2000;Schmidt, 2000).…”
Section: Case Example In Supervisionmentioning
confidence: 99%